Pelatihan Strategi Pemasaran Digital dan Penyusunan SOP untuk Meningkatkan Daya Saing UMKM Keramik Plered - Ferdiansyah, Fahmi Reza; Solihin, Rici; Dagustani, Dani (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance MSME owners' understanding of marketing strategies, digital marketing, local cultural identity–based branding, and standard operating procedure (SOP)-based business management to strengthen the competitiveness of Plered Ceramic MSMEs. The program was implemented through a series of awareness sessions, training, mentoring, and evaluation activities. The training covered market segmentation, targeting, and positioning (STP), online selling strategies, marketplace utilization, digital promotion, product content development, and the preparation of simple standard operating procedures (SOPs). Program effectiveness was evaluated using pre-test and post-test instruments consisting of 10 knowledge indicators. The data were analyzed using descriptive quantitative methods by calculating the percentage of correct responses for each indicator, the mean pre-test and post-test scores, and the difference between the two. The results demonstrated a substantial improvement in participants' understanding, with the mean score increasing from 51.11% to 94.45%, representing a gain of 43.34 percentage points. Improvements were observed across all knowledge indicators, with the greatest gains in participants' understanding of marketplace utilization and the concept of standard operating procedures. Overall, the program represents an important initial step toward strengthening digital marketing capabilities, reinforcing consistent branding practices, and promoting more structured business management among Plered Ceramic MSMEs.